Implications of Mixed Marriage in the Perspective of Gorontalo Customary Law and Its Reality based on International Private Law Principles - Mutia Cherawaty Thalib (Jambura Law Review, 2023)
This paper aims to describe the application of local wisdom values as part of the implementation of the Gorontalo Marriage Customary Law to mixed marriages performed by Indonesian citizens of Gorontalo ethnicity and foreign nationals and to analyze the consequences of mixed marriages according to Gorontalo customary marriage law. The method of data collection was carried out through the stages of inventorying secondary data, tracking primary data through interviews, in-depth focus group discussion, and then analysis qualitatively. This paper uses descriptive analytic methods. The discussion demonstrates that mixed marriage is a family law event that has occurred from time immemorial. It's just that people's understanding of the order of family life is getting wider. This is due to the fact that cross-country personal relations are getting better, which has implications for the family law order from the perspective of local wisdom, especially in regions where the family system is open to other legal systems, including Gorontalo's customary marriage law. Mixed marriages, in the view of the local wisdom of the Gorontalo people, can be carried out through the Gorontalo traditional wedding procession in full if the husband and/or wife submit to the Islamic religion. This is legally obligatory because of the philosophy of Gorontalo customs: "Adati Hula-Hulaa To Syara, Syara Hula-Hulaa To Qurani" (Adat is based on Syara, Syara is based on the Al-Quran), so that every wedding procession that chooses to use Gorontalo's customs contains advice and prayers (for God's sake), which have the value of guidance as stipulated in the Al-Quran. As for the consequences of mixed marriages on Gorontalo's customary law, where one of the bride and groom is a foreigner but not Muslim, they cannot be married according to Gorontalo's customary law; the process is based on Al-Quran values.